Políticas educacionais de alfabetização na Paraíba e seus processos de objetivação no município de Zabelê-PB (2012-2023) - Ferreira, Rafael de Farias (2024)
This investigative study aims to understand how political events and historical occurrences directly and indirectly influence the formulation and implementation of literacy education policies at the national, state, and municipal levels, with an emphasis on the State of Paraíba and a municipality located in the semi-arid region of Cariri (2012-2023). Guided by the central question: “How did the process of implementation of public literacy education policies occur in the municipality of Zabelê (PB)?”, this study seeks to comprehend how institutional agents organize the rules, procedures and mediations that regulate the relations between public authorities and society in the effective process of implementing these policies. Methodologically, this study employs a dialectical logic, drawing on the principles of historical and dialectical materialism to understand the role of literacy education policies within a society increasingly influenced by postmodern perspectives on the matter. The intensification of neoliberalism in state policies has led to the diffusion of the managerialist perspective within the educational agenda. In this context, schools have come to be conceived as a type of organization, granting the managers the status of a business administrator. Through ongoing professional development programs designed by the literacy programs, literacy teachers began to reproduce the control mechanisms that regulate the teaching and learning processes of the literacy cycle. The promotion of educational accountability, underpinned by public management principles such as legality, transparency, impartiality, and publicity, has become the core justification for state-driven actions. As a result, the quality of education is measured by external evaluations, which are closely tied to the assessment of the efficiency of the school as a production unit. Due to this prerogative, schools become the spaces that implement the actions that will self-determine whether the management was of low or high productivity. As a result of this, the predominance of fragmentation and overspecialization end up hindering the processes of implementation of literacy policies in the State of Paraíba. Using participatory research techniques, a case study was conducted in a municipal school. The investigation concludes that literacy education policies, when anchored in and guided by critical pedagogical perspectives, foster democratic processes of access to knowledge within schools. In this regard, a literacy process driven by transgressive critical acts can disrupt the exclusionary social logic that marginalizes the lower classes and the children of the working class, depriving them of access to the knowledge produced by humanity in its societal life.